An experiment with spiral wound reverse osmosis membranes for the Desalination of seawater - M.N.A. Hawlader Hawlader,; J.C. Ho Ho, and; K.T. Chua (Universitas Gadjah Mada, 2001)
In the research, the performance characteristics of Reverse Osmosis (RO) Spiral Wound (SW) membrane are evaluated. The effects of feed water concentration, temperature, pressure and flow rate on the performance of this membrane are investigated. The product recovery () of SW membrane is found to increase with feed water temperature and pressure, but decrease with increasing feed water concentration and flow rate. Salt passage (SP) increases with feed water temperature and concentration, but decreases with increasing feed pressure and flow rate. Under the tested feed water conditions, of SW varies from 6% - 18% and permeate salinity is approximately 130ppm. In addition, validity of the Complete Mixing Model is verified and successfully extended to the derivation of water and salt transport parameters of SW membrane. Plots of I/SR' versus l/Jw display linear relationships, as predicted in the model.